2012
DOI: 10.1515/jpm-2012-0107
|View full text |Cite
|
Sign up to set email alerts
|

Defining hypoxic ischemic encephalopathy in newborn infants: benchmarking in a South African population

Abstract: The incidence and grade of HIE can vary more than 2-fold in the same population, depending on which defining criteria are used. Consensus definitions are needed for benchmarking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…In-hospital mortality was low (60/450, 13.3%), with the burden anticipated to be in the disabled survivors. Our rates of perinatal asphyxia and HIE were similar to those found by Horn et al [12] The 5-minute Apgar score is a poor indication of cerebral injury. In this study, 103 babies (22.9%) had no evidence of HIE, although 347 (77.1%) had signs of neurological compromise recorded.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In-hospital mortality was low (60/450, 13.3%), with the burden anticipated to be in the disabled survivors. Our rates of perinatal asphyxia and HIE were similar to those found by Horn et al [12] The 5-minute Apgar score is a poor indication of cerebral injury. In this study, 103 babies (22.9%) had no evidence of HIE, although 347 (77.1%) had signs of neurological compromise recorded.…”
Section: Discussionsupporting
confidence: 90%
“…Horn et al [12] discuss the difficulties in consensus definitions and criteria of HIE. The data show that there is a wide variation in the incidence and grade of HIE, depending on which criteria are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth asphyxia results in significant morbidity and is the third most common (23%) global cause of death in the neonatal period . Although it has not been well documented in sub‐Saharan Africa, two studies r eported an incidence of hypoxic‐ischaemic encephalopathy (HIE) resulting from birth asphyxia that ranged between 3.8 and 8.3 per 1000 live births in two different regions in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HIE in developed countries is estimated to be 1.5 per 1,000 live births [3]. Estimates in developing countries range from 2.3–26.5 per 1,000 live births [4,5]. A recent meta-analysis found that therapeutic hypothermia commenced by age 6 hours for infants with moderate or severe (moderate-severe) HIE, significantly reduces death or disability: in three studies an abnormal amplitude integrated electro-encephalogram (aEEG) was required as an additional criterion for cooling [6].…”
Section: Introductionmentioning
confidence: 99%